Improving teaching and learning through experiential learning - McDonald, Betty (Cambridge Scholars Publishing, 2020)
Who doesnt want to improve teaching and learning? A lot of people continue to ask searching questions like: Will I ever use this in real life? Why waste time learning all this stuff? Such questions are never-ending. This book provides answers to these and many other queries. Repeatedly, we hear sayings like, No pain, no gain; Youll know it when you feel it; You have to experience it to know about it; Experience teaches!; and Experience is the best teacher! Such commonly heard adages appear to underscore the importance of experiential learning. Underpinning these aphorisms is the common theme that learning is most effective through experience. This book provides the reader with the tools needed to make better use of experiences to improve teaching and learning. It is divided into several parts to facilitate easy understanding. Operating under the Creative Commons Copyright license, the text is intentionally interspaced with relevant shareware graphics (exhibits) from the public domain. Such exhibits are selected to serve as stimulants for innovation, engagement and personal pleasure.